A meta-analysis of the effectiveness and side effects of hip arthroscopy and open surgical dislocation in the management of femoroacetabular impingement - Chenlie Ni; Haiqing Lin; Haibo Yin (BMC Musculoskeletal Disorders)
Abstract Background The influence of femoroacetabular (FA) impingement has been implied in early hip osteoarthritis, particularly in young patients who enjoy athletics. The purpose of this meta-analysis is to assess the effectiveness and safety of hip arthroscopy compared to open surgical dislocation for the treatment of femoroacetabular impingement (FAI), based on clinical trials that have been published. Methods A comprehensive literature search was conducted through PUBMED, EMBASE, and the Cochrane Central Register of Controlled Trials for studies evaluating coxoscopy and open surgical dislocation as treatment modalities for femoroacetabular impingement syndrome (FAI). Results Ultimately 9 studies were added in this meta-analysis. 9 studies reported the Improvement of alpha angle of the Hip Arthroscopy treatment group and the surgical treatment group, which was no remarkable statistical significance(SMD: -5.54; 95% Cl: -12.45,1.38; P = 0.117) compared to the surgical treatment group, Modified Harris Hip Score (mHHS) after 12 months of follow-up(SMD: 0.94; 95% Cl: -2.87,4.75; P = 0.629), Nonarthritic Hip Score (NAHS) after 12 months of follow-up (SMD:6.31; 95% Cl: 0.53,12.09; P = 0.032), rate of recurrence (OR: 0.48; 95% Cl: 0.29,0.82; P < 0.01), and rate of Complication (OR: 0.66; 95% Cl: 0.26,1.65; P = 0.372). Conclusion Alpha angle improvement, mHHS, NAHS after 12 months of follow-up, rate of recurrence, and rate of Complication are some of the indicators of the study’s results point to the possibility that hip arthroscopy may be effective for patients with FA impingement; hence, these conclusions required to be corroborated by additional superior-quality studies.